A mucin-like peptide from Fasciola hepatica instructs dendritic cells with parasite specific Th1-polarizing activity - Noya, Verónica (2017)
Fasciolosis is a trematode zoonosis of interest in public health and cattle production. We report here the immunostimulatory effect of a 66 mer mucin-like peptide from Fasciola hepatica (Fhmuc), which synergizes with lipopolysaccharide (LPS) to promote dendritic cell (DC) maturation, endowing these cells with Th1-polarizing capacity. Exposure of DCs to Fhmuc in presence of LPS induced enhanced secretion of pro-inflammatory cytokines and expression of co-stimulatory molecules by DCs, promoting their T cell stimulatory capacity and selectively augmenting IFN- secretion by allogeneic T cells. Furthermore, exposure of DCs to Fhmuc augmented LPS-induced Toll-like receptor (TLR) 4 expression on the cell surface. Finally, Fhmuc-conditioned DCs induced parasite specific-adaptive immunity with increased levels of IFN-gamma secreted by splenocytes from vaccinated animals, and higher parasite-specific IgG antibodies. However, DC-treated Fhmuc conferred modest protection against F. hepatica infection highlighting the potent immuno-regulatory capacity of the parasite. In summary, this work highlights the capacity of a mucin-derived peptide from F. hepatica to enhance LPS-maturation of DCs and induce parasite-specific immune responses with potential implications in vaccination and therapeutic strategies.